Standardization of Myristicin in Nutmeg (Myristica fragrans Houtt.) Fruit using TLC-Densitometric Method - Daniella Elizabeth Engel; Sudjarwo; Sukardiman (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2024)
Background: Myristica fragrans Houtt. (Myristicaceae family), with the main content of myristicin, has been immensely used in herbal medicine. Standardization is essential to ensure the safety of natural extracts and the quality of herbal medicines using various chemical analysis techniques. Method validation is necessary to ascertain the reliability and reproducibility of the method. Myristicin is a member of the phenylpropene group, a natural organic compound found in small amounts in nutmeg fruit, which has pharmacological effects. Objective: This study aims to determine the myristicin content in nutmeg fruit using TLC-Densitometry. Methods: Determination of myristicin in nutmeg fruit extract was performed using TLC-Densitometry with silica GF254 as stationary phase, mobile phase n-hexane: ethyl acetate (8:2 v/v), and spot visualized at 285 nm. In this study, the content of myristicin in nutmeg fruit was determined using compendial methods (AOAC), thus requiring method verification with parameters including selectivity, linearity, precision, LOD, and LOQ. Results: The validation of this method showed good linearity and selectivity with y = 0.0001x + 0.0226 (r = 0.9996) and 1.53 (>1.5), respectively. The LOD and LOQ results were low with values of 0.11 μg/spot and 0.33 μg/spot, respectively. The percentage coefficient of variation for precision was below the requirement value of not more than 4%. The average myristicin content in nutmeg fruit extract was approximately 0.0017 ± 0.0003% (w/w). Conclusion: The developed method was valid and sensitive for the quantification of myristicin content in nutmeg fruit.